Carrier photogeneration, drift and recombination in a semiconducting carbon nanotube network. Issue 34 (15th August 2017) - Eckstein, A.; Bertašius, V.; Jašinskas, V.; Namal, I.; Hertel, T.; Gulbinas, V.
Abstract : Photocurrent kinetics in SWNT–PCBM networks is governed by intra- and intertube hole drift on the 2 ns and microsecond timescales, respectively. Abstract : Charge carrier photogeneration, drift and recombination in thin film networks of polymer-wrapped (6, 5)-single-wall carbon nanotubes (SWNTs) blended with phenyl-C61-butyric acid methyl ester (PCBM) have been investigated by using transient photocurrent and time-delayed collection field (TDCF) techniques. Three distinct transient photocurrent components on the nano- and microsecond timescales have been identified. We attribute the dominant (>50% of total extracted charge) ultrashort photocurrent component with a decay time below our experimental time-resolution of 2 ns to the intratube hole motion. The second component on the few microsecond timescale is attributed to the intertube hole transfer, while the slowest component is assigned to the electron drift within the PCBM phase. The hole drift distance appears to be limited by gaps in the nanotube percolation network rather than by hole trapping or recombination. Photocurrent saturation was observed when excitation densities reached more than one charge pair per nanotube; we attribute this to the local electric field screening.